2017
DOI: 10.1080/10408398.2017.1392287
|View full text |Cite
|
Sign up to set email alerts
|

The scientific basis for healthful carbohydrate profile

Abstract: Dietary guidelines indicate that complex carbohydrates should provide around half of the calories in a balanced diet, while sugars (i.e., simple carbohydrates) should be limited to no more than 5-10% of total energy intake. To achieve this public health goal a collective effort from different entities including governments, food & beverage industries and consumers is required. Some food companies have committed to continually reduce sugars in their products. Different solutions can be used to replace sugars in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 110 publications
(110 reference statements)
1
22
0
Order By: Relevance
“…Other cultivars (e.g., 'Mansa,' 'Marrone della Val di Susa,' and 'Neirana della Val di Susa') showed higher contents of fructose than glucose. The higher fructose amount compared to the glucose one may be important to define chestnuts as a potential functional food for consumers suffering from type 2 diabetes, as fructose shows a lower glycemic index than glucose and, consequently, the postprandial glycemic peak due to fructose is lower than the glycemic peak due to glucose, as well as the insulin response [82]. As evidenced by the Tukey's test, the 'Mansa' cultivar significantly differed (p < 0.05) from the other samples, followed by 'Canepina', as mentioned above, and 'Brunette' and 'Gentile', which reported quantities close to 50 g•kg −1 DW.…”
Section: % 10% 20% 30% 40% 50% 60% 70% 80% 90% 100%mentioning
confidence: 99%
“…Other cultivars (e.g., 'Mansa,' 'Marrone della Val di Susa,' and 'Neirana della Val di Susa') showed higher contents of fructose than glucose. The higher fructose amount compared to the glucose one may be important to define chestnuts as a potential functional food for consumers suffering from type 2 diabetes, as fructose shows a lower glycemic index than glucose and, consequently, the postprandial glycemic peak due to fructose is lower than the glycemic peak due to glucose, as well as the insulin response [82]. As evidenced by the Tukey's test, the 'Mansa' cultivar significantly differed (p < 0.05) from the other samples, followed by 'Canepina', as mentioned above, and 'Brunette' and 'Gentile', which reported quantities close to 50 g•kg −1 DW.…”
Section: % 10% 20% 30% 40% 50% 60% 70% 80% 90% 100%mentioning
confidence: 99%
“…Most Ghanaian meals are mainly composed of carbohydrate [18] and grouping them according to their distinct glycemic response has wiped away the notion that foods that are rich in carbohydrates are not suitable for persons with metabolic diseases such as diabetes and obesity. Studies have shown that carbohydrates are of different quality [1,5]. According to a study conducted by Bornet et al [19], even though glucose has a nauseating effect after it has been ingested, it remains the reference material that has no variation in its preparation as compared to white bread which showed different mode of preparation in different study areas.…”
Section: The Gi Values Of Test Mealsmentioning
confidence: 99%
“…Carbohydrates are one of the three energy-yielding macronutrients required for the optimum functioning of the human body [1]. They provide energy for the body, especially the brain and the nervous system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 21st century, an interest in food formulations containing complex polysaccharides continues to rise, owing to the bioactivities and health-promoting functions of these polysaccharides [1,2]. Polysaccharides are an indispensable component of many foods.…”
Section: Introductionmentioning
confidence: 99%